Shared cluster resources as a source of capabilities - Cardeal, N.; Abecassis-Moedas, C.; António, N. (International Journal of Entrepreneurship and Small Business, 2014)
Abstract: Literature on clusters acknowledges the existence of resources that are shared by firms in the same cluster. The literature on dynamic capabilities argues that in the context of capability development, firms need to develop different business models and to define their firm boundaries in complementary ways. We use a multiple case study approach to analyse how three small- and medium-sized firms belonging to the same cluster but with different business models have been using cluster resources. We find that the some resources are not used in the same way nor for the same purpose. Our inductive investigation leads to two propositions: shared resources that are used the same way by all the cluster firms are not a source of core capabilities to the firms; and shared resources that are used differently by the firms in the cluster are a source of dynamic capabilities which have an impact on the business model.